Shadows of colonialism: the rejection of France in the Sahel - Chaumont, Flore Marie Cleophe (2024)
This thesis explores the complex dynamics and historical factors that led to an increase in resentment and opposition towards French presence and military intervention in the Sahel region, focusing on Mali, Burkina-Faso and Niger. It analyses the colonial heritage, contemporary French policies and military strategic failures of Barhane, as well as the mergence of new geopolitical actors offering an alternative to France and working to diminish the influence of the West in Africa. Basing off literature review, semi-structured interviews, and an analysis of the news, this thesis aims to contribute to a better understanding of the contemporary challenges in Afro-french relations in the Sahel. The paper will try to answer the following research question “What are the key factors contributing to the growing resentment and opposition towards France's presence and military intervention in the Sahel region?". To achieve this, we will begin by offering a detailed background on the colonial and post-colonial history of the studied countries. We will then examine the relationships between France and these countries during and after the Cold War. We will then assess their interactions in the 21st century. Finally, we will explore the roles of other significant geopolitical actors influencing the region.